Burden of Comorbidity in Systemic Lupus Erythematosus in the UK, 1999–2012. Issue 6 (26th May 2016) - Rees, Frances; Doherty, Michael; Grainge, Matthew; Lanyon, Peter; Davenport, Graham; Zhang, Weiya
Abstract : Objective: To estimate the comorbidity associated with systemic lupus erythematosus (SLE) in the UK during 1999–2012. Methods: A retrospective cohort study using the UK Clinical Practice Research Datalink was conducted. Prevalent cases of SLE were matched by age, sex, and practice to 4 controls. The incidence of cardiovascular disease (CVD), stroke, end‐stage renal failure (ESRF), cancer, osteoporosis, and infection were calculated per 1, 000 person‐years during the study period and compared to controls using Poisson regression to obtain incidence rate ratios (IRRs). IRRs were adjusted for baseline age, sex, body mass index, smoking status, alcohol intake, hypertension, hyperlipidemia, Charlson Index scores, and prednisolone use. Age‐ and sex‐specific incidence rates were calculated. Results: When comparing the 7, 732 prevalent cases of SLE with 28, 079 matched controls, the unadjusted IRR was 1.98 (95% confidence interval [95% CI] 1.69–2.31) for CVD, 1.81 (95% CI 1.49–2.19) for stroke, 7.81 (95% CI 4.68–13.05) for ESRF, 1.28 (95% CI 1.17–1.40) for cancer, 2.53 (95% CI 2.27–2.82) for osteoporosis, and 1.49 (95% CI 1.40–1.58) for infection. After adjustment, the rates remained significantly higher in cases. Men with SLE had higher rates of CVD, stroke, and cancer, whereas women had higher rates of infection and osteoporosis. Those at younger ages were at the greatest relative risk compared with controls. Cases had significantly higher Charlson Index scores at baseline. Conclusion: People with SLE in the UK have a greater burden of comorbidity and are more likely to develop CVD, stroke, ESRF, cancer, osteoporosis, and infection than people of the same age and sex.